DO PRIMARY SCHOOL STUDENTS LIKE MATHEMATICS? - Vragović, Anica; Klasnić, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Importance of mathematics as a school subject is evident in a fact that it is a constituent part of core curriculum for basic education in all education systems in the world. First few years of education are of crucial importance to the formation of attitudes towards mathematics. Attitudes are important because they navigate our actions and by doing so, influence our reality and our future as well. Research on attitudes towards mathematics has considerably increased over the past few years, since the importance of mathematics is getting continuously more accentuated. In the context of schools and education, it is emphasized how positive attitude towards mathematics influences students’ relationship with school-work, studying, confidence and behaviour. The aim of the study was to determine primary school students’ attitudes towards mathematics. One hundred and seventy-one students from 3rd to 8th grade from III Primary School Varaždin, Croatia participated in the research. The data were analyzed with t-test and one-way ANOVA for independent samples. The research has shown that there is no statistically significant gender difference in attitudes towards mathematics; however, age difference was confirmed. It was also found that younger students in primary education had a more positive attitude towards mathematics than older students. Practical implications of acquired results could be in providing additional support to 5th and 6th grade students when the change from positive to negative attitude happens.